A organização de programas e projetos ecológicos na Amazônia: um desafio para a ciência da administração - Erismann, Eduardo de Magalhães (1997)
This thesis explains the question of a substantive rationality and its importance for ecological and sustainable projects and programs lt discusses some of this projects, which are located in the Manaus region, demonstrating organizational and financing aspects.